Interrelation of Economic and Political Crises in Russia as Reason of the February Revolution of 1917 - A. V. Chernyshova (Управленческое консультирование)
In the article on the basis of statistical materials and documents of the organs of state administration the problems in the economy, the social sphere and the political life of Russia at the beginning of the centuries XX, which were aggravated under the effect of the world war, are revealed. It shows, as the interrelation of data of problems, it brought at the end of February 1917 of year to the general national crisis and a drop in the monarchy in the Russian Empire by revolutionary way. It proves that the permission of crisis via reforms proved to be impossible, since authority proved to be not capable of the reformatory activity. Are represented reasons and nature of the formation of antigovernment opposition in different layers of the society: among the workers, the peasants, the owner’s and liberal bourgeoisie. The nature of the opposition of the supporters of monarchy and state thought is shown. Is done the conclusion that the February revolution was under such conditions inevitable.